Social Support for Secondary School Students - Azeez, Awan Kadim; Talal, Fatima Ismail (Journal of Tikrit University for Humanities, 2023)
The current research aims to identify the level of social support among high school students. Differences are statistically significant in social support depending on the gender variable (male-female) among high school The differences are statistically significant in school and social support depends on the variable of specialization (scientific-literary) among high school students. The research sample consists of (400 students) from salah al-Din high schools/ Tikrit district. The researcher has adopted Al- Ahbabi Scale which entails (35) Paragraphs, distributed in three areas (Social emotional support, Effective social support, Informational social support. ) Five alternatives to the response have been developed for each paragraph. Stability has been calculated in a retested manner of 0.79 and is a good stability factor. High school students enjoy a good level of Social support. 1.There is no effect of sex on the Social support school students. 2.There is no effect of specialization on the Social support school students. 3.Through the results, the researcher made a number of recommendations and proposals.